Differences between women and men in prolonged weaning - Röser, Evelyn; Michels-Zetsche, Julia D.; Ersöz, Hilal; Neetz, Benjamin; Höger, Philipp; Trinkmann, Frederik; Müller, Michael; Klotz, Laura Valentina; Kontogianni, Konstantina; Winter, Hauke; Dahlhoff, Jana Christina; Krysa, Sabine; et al. (Respiratory research, 2024)
In recent years, the importance of sex as a factor influencing medical care has received increasing attention in the field of intensive care medicine. The objective of this study was to examine the influence of sex in prolonged weaning.
Gesehen am 27.03.2025